Socioeconomic Dynamics of the Bunyu Island Community-North Kalimantan: Baseline Studies for the Launch of the Corporate Social Responsibility (CSR) Program - Safrizal Rambe; Zulkarnain (Budapest International Research and Critics University, 2022)
This research is a mapping of the socioeconomic dynamics of the people of Bunyu Island, North Kalimantan, which is helpful as baseline studies when community development programs and other development programs are launched. Socioeconomic mapping of the community becomes important when we often see various government development programs and the private sector being criticized for not being based on the community's actual needs. This research shows how the socioeconomic dynamics of the people of Bunyu Island, economic characteristics, culture, socio-political dynamics, and various other things are expected to describe the socioeconomic conditions of the people of Bunyu Island. Bunyu itself is an area with firm characteristics. Its geographical environment is in the form of a small island, but it is known for its extraordinary natural wealth. Since the Dutch era, it has been known as an oil-producing island, and recently it is also a coal-producing area.